2014
DOI: 10.1063/1.4896760
|View full text |Cite
|
Sign up to set email alerts
|

Potential variations around grain boundaries in impurity-doped BaSi2 epitaxial films evaluated by Kelvin probe force microscopy

Abstract: Hard x-ray photoelectron spectroscopy study on valence band structure of semiconducting BaSi2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…In the past, several impurity dopant candidates were attempted either to make an n‐type or a p‐type BaSi 2 thin film by using group 11 elements (Cu and Ag ), group 13 elements (B , Al , Ga , and In ), and group 15 elements (P , As , and Sb ). In line with the theoretical expectation , BaSi 2 films doped with group 13 elements except Ga exhibit n‐type conductivity, while those with Cu or group 15 elements exhibit p‐type conductivity. Table summarizes the carrier type and the maximum carrier concentrations at RT achieved by molecular beam epitaxy (MBE) or ion implantation into MBE‐grown BaSi 2 films.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the past, several impurity dopant candidates were attempted either to make an n‐type or a p‐type BaSi 2 thin film by using group 11 elements (Cu and Ag ), group 13 elements (B , Al , Ga , and In ), and group 15 elements (P , As , and Sb ). In line with the theoretical expectation , BaSi 2 films doped with group 13 elements except Ga exhibit n‐type conductivity, while those with Cu or group 15 elements exhibit p‐type conductivity. Table summarizes the carrier type and the maximum carrier concentrations at RT achieved by molecular beam epitaxy (MBE) or ion implantation into MBE‐grown BaSi 2 films.…”
Section: Introductionsupporting
confidence: 85%
“…Boron (B) was chosen as an impurity candidate in BaSi 2 to fabricate p‐type BaSi 2 epitaxial layers. Recently, after theoretical investigation of B‐doped BaSi 2 thin films, it was found that not only the Si substitution with B but also the interstitial insertion of B into the 4c site is energetically favorable . It was speculated that this difference comes from a smaller atomic radius of B than those of Sb‐, Al‐, and In‐atoms in BaSi 2 .…”
Section: Resultsmentioning
confidence: 99%
“…31,32 We have attributed the high L and pronounced photoresponsivity of undoped n-BaSi 2 on Si(111) to the downward band bending at the DBs, as determined by Kelvin probe force microscopy, which may restrict photogenerated minority carriers (holes) from the DBs. 33,34 In contrast, upward band bending is observed at the DBs in the case of BaSi 2 on Si(001), 33 meaning that the photogenerated minority carriers are directed toward defective DBs. Planview transmission electron microscopy (TEM) observations have shown that there are numerous defective DBs in BaSi 2 on Si(001), whereas many sharp straight DBs parallel to the (011) or (0-11) planes are found in BaSi 2 on Si(111).…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, extensive studies have been conducted on GBs in solar cell materials, such as polycrystalline Si and chalcopyrite semiconductors in an attempt to improve efficiency. According to our previous investigations, 32,33 the electrostatic potentials were higher at GBs in undoped n-BaSi 2 and lightly Sb-doped n-BaSi 2 epitaxial films on Si(111) than those in the BaSi 2 grain interiors by approximately 10-30 mV. This downward band bending at the GBs is beneficial for n-type BaSi 2 , because the minority carriers (holes) are not attracted toward the GBs, which enable the suppression of minority-carrier recombination at the GBs.…”
Section: Introductionmentioning
confidence: 99%